A reversible underwater glue based on photo- and thermo-responsive dynamic covalent bonds. Issue 1 (25th September 2019) - Wang, Zhao; Guo, Lifeng; Xiao, Hongyan; Cong, Huan; Wang, Shutao
Abstract : A reversible underwater glue exhibits strong and widely tunable adhesion in response to orthogonal photo- and thermal stimuli. Abstract : The intriguing reversible underwater adhesive phenomena in nature have inspired the rapid development of artificial adhesives by microscopic topography engineering or chemical modification on solid surfaces. However, most of the existing reversible underwater adhesives often suffer from low adhesion strength or complex fabrication processes. Here we present a reversible underwater glue by incorporating photo- and thermal-responsive anthracenyl moieties into an adhesive polyethylenimine backbone, featuring strong, widely tunable adhesion strength from 50.5 ± 7.4 to 606.7 ± 30.3 kPa, desirable fluidity, and compatibility to various substrates. Under orthogonal photo- and thermal stimuli, the reversible anthracene dimerization endows dynamic forming and breaking of cross-linked polymer networks within the glue, leading to reversible adhesion between solid substrates. Moreover, the glue can spontaneously spread over solid surfaces and absorb interfacial water molecules to realize adequate contact, promoting strong adhesion to diverse substrates and liquid environments. This study will provide an important strategy to develop the next generation of smart underwater adhesives.